PLANAR HEXAGONAL LOOP ANTENNA DESIGN AND IMPLEMENTATION FOR UNDERWATER OFDM COMMUNICATION SYSTEM - Salman Al-Faruq, Muhammad
This research focuses on designing a compact antenna for underwater communication between Autonomous Underwater Vehicles (AUVs) and dock stations at close range. The proposed antenna is a 39.18 cm x 39.98 cm hexagonal loop planar antenna. The RF communication utilizes a VHF band frequency. Measurement results show that the antenna has reflection coefficient of -20 dB at frequency of 44 MHz and bandwidth of 24 MHz. The performance of the RF communication system is tested on bit transmission and text communication using underwater OFDM. The RF communication system produced an exemplary constellation diagram and successfully received the transmitted text data.